SINERGISTA (Agrotourism Synergy): A Sustainable Tourism Development Strategy Based on Digitalization Through the Pentahelix Collaboration Model to Support the 2030 SDGs - Ramadhan, Dede; Ahleyani, M.; Lestari, I Gusti Ayu Cintiya Widya; Ramadhan, Hafiz Okta; Yolanda, Steviani (Eastasouth Institute, 2025)
Sustainable tourism is a key pillar in achieving the Sustainable Development Goals (SDGs) 2030. This study introduces SINERGISTA (Sinergi Agrowisata) as a digital-based sustainable tourism development strategy through a Pentahelix Connectors collaboration model involving government, academia, business actors, communities, and media. The objective of this research is to formulate an implementable strategy for digital-based agrotourism development aimed at enhancing economic, social, environmental, and cultural value in a sustainable manner. This study employs a descriptive-exploratory approach through in-depth interviews, field observations, and documentation studies on leading agrotourism destinations in Indonesia. Findings reveal that integrating digitalization into marketing platforms, reservation systems, and virtual reality promotions expands market reach, increases tourist engagement, and facilitates transparent destination management. Moreover, the Pentahelix Connectors collaboration is proven effective in reinforcing synergy among stakeholders in promoting service innovation, improving human resource capacity, and fostering participatory environmental management. Strategic recommendations include strengthening digital literacy among agrotourism actors, ensuring regional government policy support, and providing inclusive and adaptive technological infrastructure.